Preventative services offered by veterinarians on sheep farms in England and Wales: opinions and drivers for proactive flock health planning - Bellet, Camille; Woodnutt, Joanna; Green, Laura E.; Kaler, Jasmeet (Elsevier, 2015)
Recent independent UK government reports and studies have highlighted the importance, but lack, of flock health services provided by veterinarians. Qualitative interviews were analysed by thematic analysis to construct belief statements to understand veterinarians' opinions on preventative advice and drivers for current services to sheep farmers. A postal questionnaire was sent to 515 sheep practices registered with the Royal College of Veterinary Surgeon (RCVS) in England and Wales in 2012 to gather quantitative data on these belief statements and to gather demographic information and current services provided by the veterinarian. Exploratory factor analysis with heuristic approaches was conducted on the respondents' belief statements to identify common factors of veterinarian beliefs. Three main factors were identified: motivation for proactiveness, perceived capability to offer preventative services and perceived opportunity to deliver these services. A beta regression model was built to identify the factors significantly associated with the time veterinarians spent in an advisory role. The relative proportion of time increased by 10% (1.01-1.19), 16% (1.03-1.30) and 29% (CI: 1.09-1.53) for each unit increase in score for factor 1 motivation, factor 2 capability and factor 3 opportunity respectively, indicating that these latent factors explained time veterinarians spent in an advisory role with sheep clients. There was a significant correlation between these factors suggesting influence of the associated beliefs between factors. This study provides insight into the nature and drivers of veterinarians' current behaviour and beliefs. These results could be further tested in behaviour intervention studies and help in designing efficient strategies aiming at promoting proactive health services offered by veterinarians on sheep farms in England and Wales.